Language Endangerment and Language Revitalization An Introduction - Tsunoda, Tasaku (De Gruyter Mouton, 2006)
In almost every part of the world, minority languages are being threatened with extinction. At the same time, dedicated efforts are being made to document endangered languages, to maintain them, and even to revive once-extinct languages. The book presents a comprehensive overview of language endangerment and revitalization. Among the examined aspects are: degrees of endangerment, definitions of language death, causes of endangerment, types of speakers in endangerment situations, methods of documentation. The book is of interest to a wide readership, including linguists, anthropologists, sociologists, and educators.